Perspective Analysis of Traffic Safety Education Curriculum Needs in Kindergartens in Central Java - Anggoro, Ario Satyo; Wijaya, Asyhari; Fahrezy, Daffa Athariq; Brilianti, Dani Fitria (Kirana Publisher (KNPub), 2024)
Early childhood traffic safety education has become increasingly important, especially as young children are frequently exposed to road surroundings and transportation hazards. This study examines opinions regarding the curricular needs for teaching road safety in kindergartens located in Central Java. This study analyzes the needs for curriculum components and teaching methods to instill traffic awareness and safe behavior in kindergarten-aged children from the perspectives of teachers. Using a qualitative descriptive approach, data were collected via surveys distributed to kindergarten teachers, focusing on their perspectives on the necessity of traffic safety education and the appropriate curriculum components. The results revealed a strong consensus on the importance of introducing traffic safety education at an early age. Respondents emphasized the need for interactive teaching methods, such as games and visual media, to convey traffic rules and safe behaviors effectively. Over 94% of respondents agreed that basic traffic symbols, pedestrian safety, and road risk awareness should be integrated into early education to foster disciplined and safety-conscious habits among children. The study concludes that a comprehensive traffic safety curriculum in kindergartens is vital for reducing traffic-related risks in the future. It recommends the development of interactive, age-appropriate materials, and emphasizes collaboration between schools, families, and communities to reinforce safety practices beyond the classroom. This integrated approach is essential to shaping a culture of safety among the younger generation.